The origin of Chinese glasses and the glass trade along the Silk Road from the Warring States (475 BC – 221 BC) to the Han Dynasty (202 BC – AD 220) - Ma, Q (2021)
The Silk Roads played significant roles in the trade of glass products. Natron glass from the Mediterranean, potash glass and mineral soda alumina glass from South and Southeast Asia have been discovered in different provinces in China. This article-based thesis mainly consists of three individual papers.